Returns on Initial Public Offerings of Closed-End Funds - Peavy, John W. (Review of Financial Studies, 1990)
Examination of 41 closed-end fund intial public offerings (IPOs) during the period from January 1986 to June 1987 reveals that the mean intial day's return is not significantly different from zero in contrast to previous findings for nonfund IPOs. New funds also show significant negative after- market returns unlike other new issues. Despite the disparity between our findings and previous results, our results are consistent with existing models. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.